Strong sense of coherence contributes to successful aging and higher satisfaction with life - Kocjan, Janusz (Journal of Education, Health and Sport, 2017)
Sense of coherence (SOC) is a core concept within Antonovsky’s salutogenic theory and is argued to be a psychological determinant of health. Salutogenic approach proposed by Antonovsky emphasized the importance of coping resources in dealing with stress. The general objective of the study was to empirically explore the relationship between the generalized resistance resources of sense of coherence with successful aging and satisfaction with life. The sense of coherence (SOC-29), life satisfaction (SWLS) and successful aging (SAS) was assessed in a sample of N = 67 participants aged 80 years or older. The present study reveals that strong SOC is associated with better life satisfaction and better successful aging. Interaction effect of age to SOC was no found. Overall, the findings provided support that SOC is an important salutary resource in association with life satisfaction and successful aging among older people.